Clinicopathological characterisation of renal cell carcinoma in young adults: a contemporary update and review of literature. Issue 6 (27th April 2020) - Abdulfatah, Eman; Kennedy, John M; Hafez, Khaled; Davenport, Matthew S; Xiao, Hong; Weizer, Alon Z; Palapattu, Ganesh S; Morgan, Todd M; Mannan, Rahul; Wang, Xiao‐ming; Dhanasekaran, Saravana M; Kaffenberger, Samuel D; et al.
Abstract : Aims: Renal cell carcinomas are relatively rare in children and young adults. While well characterised in adults, the morphological and molecular characterisation of these tumours in young patients is relatively lacking. The objective of this study was to explore the spectrum of renal cell carcinoma (RCC) subtypes in children and young adults and to determine their clinico–pathological, immunohistochemical and molecular characteristics by evaluating a large retrospective cohort of renal cell carcinoma patients age 30 years or younger. Methods and results: Sixty‐eight cases with confirmed diagnosis of renal cell carcinoma at age 30 years or younger were identified at our institution. Clear cell carcinoma accounted for the most common subtype seen in this age group. Translocation renal cell carcinoma and rare familial syndrome subtypes such as succinate dehydrogenase deficient renal cell carcinoma and tuberous sclerosis complex‐associated renal cell carcinoma were found relatively more frequently in this cohort. Despite applying the 2016 WHO classification criteria, a high proportion of the tumours in our series remained unclassified. Conclusions: Our results suggest that renal cell carcinoma in children and young adults is a relatively rare disease that shares many histological similarities to renal cell carcinoma occurring in adults and yet demonstrate some unique clinical–pathological differences. Microphthalmia‐associated transcription (MiT) family translocation RCC and rare familial syndrome subtypes are relatively more frequent in the paediatric and adolescent age groups than in adults. Clear cell RCC still accounted for the most common subtype seen in this age group. MiT family translocation RCC patients presented with advanced stage disease and had poor clinical outcomes. The large and heterogeneous subgroup of unclassified renal cell carcinoma contains phenotypically distinct tumours with further potential for future subcategories in the renal cell carcinoma classification.